The role and efficacy of clozapine treatment in early-onset and very early-onsetschizophrenia cases: discussion of five cases - Perçinel, İpek; Yazıcı, Kemal Utku; Erermiş, Hatice Serpil; Özbaran, Burcu; Köse, Sezen Gökçen; Zemla, Joanna; İdris, Bülent (My University, 2015)
Schizophrenia is a serious mental disorder emerging at an early age, characterized by significantbreakdowns in thought, perception and behavioral processes and withdrawal from humanrelationships. Psychopharmacologic and psychosocial approaches should be combined for thetreatment of schizophrenia. Although the effects and side effects of both typical and atypicalantipsychotics have been studied in adult patients in detail, studies in child and adolescentage groups are inadequate. Clozapine is a prototype of atypical antipsychotics and the firstantipsychotic to be defined as atypical. Clozapine is often effective in cases in which typicaland other atypical antipsychotics fail, and is accepted as the gold standard in the treatmentof schizophrenia. In this paper, the effects and side effects of clozapine in five adolescentcases diagnosed with schizophrenia are discussed. Four of these cases showed that clozapineis effective in adolescent schizophrenia. While the four cases showing good responses to thetreatment tolerated clozapine well, the other case (case 4) showed an apparent decreasing trendin neutrophil count a short while after starting the treatment and his medication was stoppedat the request of his parents.
Keywords: Psikiyatri